2009
DOI: 10.1002/stem.3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Phosphoinositide 3-Kinase-Dependent Transcriptome in Murine Embryonic Stem Cells: Identification of Novel Regulators of Pluripotency

Abstract: Phosphoinositide 3-kinase (PI3K)-dependent signaling has been implicated in the regulation of embryonic stem (ES) cell fate. To gain further insight into the mechanisms regulated by PI3Ks in murine ES cells, we have performed expression profiling using Affymetrix GeneChips to characterize the transcriptional changes that arise as a result of inhibition of PI3K-dependent signaling. Using filtering of greater than 1.5-fold change in expression and an analysis of variance significance level of p < .05, we have de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
3
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 61 publications
5
82
3
1
Order By: Relevance
“…20 Inhibition of PI3K/Akt signaling with LY-294002 reduces mouse ES proliferation, pluripotency, and Nanog expression. 18,19,21,22 Those effects are similar to the effects of overexpressing DLK in mouse ES cells ( Fig. 3C and D).…”
Section: Dlk Kinase Activity Is Upregulated Upon Differentiation Of Msupporting
confidence: 75%
See 4 more Smart Citations
“…20 Inhibition of PI3K/Akt signaling with LY-294002 reduces mouse ES proliferation, pluripotency, and Nanog expression. 18,19,21,22 Those effects are similar to the effects of overexpressing DLK in mouse ES cells ( Fig. 3C and D).…”
Section: Dlk Kinase Activity Is Upregulated Upon Differentiation Of Msupporting
confidence: 75%
“…[18][19][20][21][22] Many proteins and signaling pathways involved in proliferation or pluripotency are modulated by PI3K/Akt including Gsk3b/Myc, FoxO, mTOR and Tbx3/Nanog pathways. 8,21,22,41-43, In this study, for the first time, DLK was demonstrated to be an Akt substrate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations